O casal - André Evangelista Marques (Medievalista)
This text is a synopsis of a master’s dissertation in Medieval History, focused on the study of the casal, regarded as an unit of space social organization, in the NW of Portugal, along the X-XII centuries. It synthesizes the guiding programme and the main results of an analysis centred on the evolution of this type of peasant holding which, alike what happened in most regions of Medieval West, was a key-element in the construction of a feudal society in Entre-Douro-e-Lima.